CADMIUM STRESS-INDUCED SENSITIVITY RESPONSES IN Peltophorum dubium - Wertonge, Gerâne Silva; Miranda Aguilar, Marcos Vinícius; da Rosa Lovato, Luana; Preussler Birck, Thalía; Bernardy, Daniele; Almeri Tabaldi, Luciane (Floresta, 2024)
Cadmium (Cd) ranks prominent position among issues observed worldwide due to its increased bioavailability that results from several polluting activities. Thus, it is necessary conducting studies focused on investigating the association between this metal and the flora, since species capable of tolerating toxic Cd levels can be indicated for the phytoremediation of contaminated areas. The aim of the present study is to investigate the tolerance of species Peltophorum dubium to excess Cd, based on the assessment of morphophysiological and biochemical variables. P. dubium seedlings were cultivated in nutrient solution with five different Cd concentrations (0, 25, 50, 75 and 100 µM) and four repetitions. Each sampling unit comprised a tray with 16 plants, and it totaled 64 plants per treatment. Morphophysiological features such as dry biomass, roots’ morphological variables, and photosynthetic variables were analyzed. In addition, photosynthetic pigment concentration, antioxidant enzymes, hydrogen peroxide (H2O2), and lipid peroxidation (MDA) concentrations were investigated. P. dubium seedlings showed toxicity symptoms, such as reduced pigment concentration and photosynthetic rate, as well as root growth and biomass production inhibition. Based on these findings, P. dubium seedlings have shown sensitivity to Cd. Therefore, this species can be used as bioindicators of cadmium-contaminated areas.